Cultural and Individual Factors Determine Physical Aggression Between Married Partners: Evidence From 34 Countries. (August 2017) - Ebbeler, Christine; Grau, Ina; Banse, Rainer
The current study compared the incidence and magnitude of physical aggression among married partners in 34 countries and examined its association with cultural factors (Gender Inequality Index, Human Development Index, Hofstede's dimensions individualism, and power distance), demographic variables (age, sex, income), and couple variables (equality in decision making). Countries were chosen on the basis of maximizing the variance of the cultural factors. Due to the high intercorrelations between the four cultural factors, simultaneous examination faced the problem of multicollinearity, while separate investigations would have led to redundant results. Therefore, an aggregated emancipation index was proposed, which is highest in countries with high human development, high individualism, low gender inequality, and low power distance. In each country, participants were asked to indicate the frequency of several types of aggression against their partner and the frequency of their partner's aggressive behavior toward them. Multilevel analysis showed that aggression level was accounted for by lower age, lower income, less equality in decision making within the couple, and lower emancipation. Being female, lower income, less equality in decision making, and less emancipation were associated with sex differences in perpetrating aggression (more male than female aggression). Interaction effects showed that equality in decision making protects from aggression and predominantly male aggression especially in countries low in emancipation.